Development of client server AI services with Mac OS - Ng, Alexander Rui Hao (Nanyang Technological University, 2024)
This project is a full stack application similar to Runway ML, a popular platform that offers Artificial Intelligence services to assist with creative projects such as image generation and image editing. The application developed in this project provides the following services - Background Removal, Super Resolution, Image Generation and Image Search and the result images can be added seamlessly to a canvas where it can be moved, resized and combined with other images to form a project.